Oral presentation Ecotoxic and mutagenic effects of photolytic transformation products of three pharmaceuticals and their mixtures: An experimental design approach - Vasquez Christodoulou, Marlen (My University, 2026)
Vasquez MI, Tarapoulouzi M, Hapeshi E, Papaphilippou P, Lambrianides N, Michael C, Lambropoulou D, Fatta-Kassinos D, Ecotoxic and mutagenic effects of photolytic transformation products of three pharmaceuticals and their mixtures: An experimental design approach, Oral presentation, 14th EuCheMS International Conference on Chemistry and the Environment, Barcelona, Spain, 25-28 June 2013.